2007
DOI: 10.1111/j.1445-2197.2007.04026.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Time to Urgent Surgery by Transporting Resources to the Trauma Patient

Abstract: A surgically supported retrieval response allows for the more timely delivery of urgent surgical care. Patients can potentially benefit from such a response. There are, however, important operational considerations in providing a surgically supported retrieval response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…McMonagle et al reviewed trauma patients transported by the air retrieval service in NSW between 1999 and 2003. 9 There were 749 interhospital patient transfers, of which 64% were from rural areas. However, only 0.4% (3) patients had a surgically supported response with an urgent surgical procedure carried out before patient transportation, which did not provide enough power to conclude whether such a surgically supported retrieval response would be cost effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McMonagle et al reviewed trauma patients transported by the air retrieval service in NSW between 1999 and 2003. 9 There were 749 interhospital patient transfers, of which 64% were from rural areas. However, only 0.4% (3) patients had a surgically supported response with an urgent surgical procedure carried out before patient transportation, which did not provide enough power to conclude whether such a surgically supported retrieval response would be cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest was the ability of the neurosurgery team to be in attendance in an emergency on‐the‐spot operation. McMonagle et al reviewed trauma patients transported by the air retrieval service in NSW between 1999 and 2003 9 . There were 749 interhospital patient transfers, of which 64% were from rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Time to definitive trauma care (particularly hemostasis requiring surgery) is known to strongly influence outcome [12]. In a previous study, researchers suggested a road distance more than 10 miles or an expected transport time more than 45 minutes by GEMS is the minimum at which helicopter transport could be faster [13].…”
Section: Discussionmentioning
confidence: 99%
“…The time to definitive trauma care strongly influences patient outcomes. 31 Any benefit associated with HEMS would likely be attributed to a reduction in the time from injury to definitive care. However, in this study, the median time from 119 is Japanese version calls to ED arrival was longer in the helicopter than in the ground group.…”
Section: Discussionmentioning
confidence: 99%